The Relationship of Paranasal Sinus Opacification to Hospital-Acquired Pneumonia in the Neurologic Intensive Care Unit Patient. (October 2019) - Huyett, Phillip; Rowan, Nicholas R.; Ferguson, Berrylin J.; Lee, Stella; Wang, Eric W.
Background: The association between intensive care unit (ICU) sinusitis and the development of lower airway infections remains unclear. The objective of this study was to determine the correlation between the development of radiographic sinus opacification and pneumonia in the neurologic ICU setting. Methods: A retrospective review of head computed tomography or magnetic resonance imaging of 612 patients admitted to the neurocritical care unit at a tertiary care center from April 2013 through April 2014 was performed. Paranasal sinus opacification was measured using Lund-Mackay scores (LMS). A diagnosis of pneumonia was determined by the ICU team from radiographic, laboratory, and pulmonary data. Exclusion criteria included a history of endonasal surgery, sinonasal malignancy, facial fractures, ICU admission less than 3 days, or inadequate imaging. Results: Worsening sinus opacification occurred in 42.6% of patients and pneumonia in 18.5% of patients during ICU admission. Of the patients who developed pneumonia, 71.7% also developed worsening sinus opacification ( P < .001). In 80.2% of cases, the sinus opacification developed prior to the diagnosis of pneumonia. The mean highest LMS for patients who developed pneumonia was 4.24 compared to 1.99 in patients who did not develop pneumonia ( P < .001). Sinus air–fluid levels or complete sinus opacification occurred in a larger proportion of patients who developed pneumonia (46.9% vs 19.4%, P < .001). Mortality rates for patients with no pneumonia or sinusitis, pneumonia only, sinusitis only, and sinusitis with pneumonia were 7.6%, 15.6%, 18.3%, and 25.9%, respectively ( P < .001). Conclusions: This study finds a strong relationship between worsening sinus opacification in the neurologic ICU patient to the development of hospital-acquired pneumonia and increased mortality.